A study of the piezocone penetrometer in normally consolidated clay - May, R (1987)
The research was intended to enhance the understanding of penetrometer behaviour in normally consolidated clay. The effects of varying penetration rate and clay shear strength were studies and the distribution of pore pressures determined. The meet these objectives laboratory testing was undertaken. Penetration tests were to be performed in tanks of clay consolidated from slurry and maintained under known stresses. An initial series of tests examined the effect of stiff tank walls. These showed unexpectedly high radial boundary stresses were generated with tank to probe diameter ratios of 50:1. This finding dictated laboratory tests with small scale penetrometers in the largest practical size of tank. Field tests with small scale and full size penetrometers demonstrated an absence of scale effect in the penetrometer pore pressures and total stress data. Two consolidation tanks of 580mm diameter and one of 1000mm diameter were built with the facility for maintaining constant stresses on top of the sample during penetration. Piezocone penetrometers of 5cm2 and 1cm2 cross-section were built. Penetration tests were performed from 2cm/s to 3m/s with hydraulic insertion equipment. At lower rates the total cone resistance factor Nkt was shown to be 10.3±0.9 in normally consolidated kaolin. The corresponding pore pressure factor NΔu was 8.25±1.0 at the cone shoulder. A hundredfold increase in the penetration rate increased the Nkt factor by 40% but the NΔu factor was unchanged. Various subsidiary points emerged. The type of strength test used for comparison with penetrometer data is significant. Major strength reductions occur on sample depressurization. These were demonstrated with vane and triaxial tests. Baligh and Levadoux’s method for determining ch from pore pressure dissipation around penetrometers matched experimental data. Ratios of excess pore pressures on the cone face and shoulder show some promise in the evaluation of OCR.